2019
DOI: 10.1002/chem.201806350
|View full text |Cite
|
Sign up to set email alerts
|

BaB2O3F2: A Barium Fluorooxoborate with a Unique [B2O3F] Layer and Short Cutoff Edge

Abstract: Substitution of oxygen by fluorine in the borate group offers am aterials platform from which intriguing structure and functionality may arise. Herein,w er eport a new fluorooxoborate, BaB 2 O 3 F 2 ,s ynthesized by introducing the Fa toms into the BaO-B 2 O 3 system.B aB 2 O 3 F 2 exhibits au nique oxyfluoride layer 2 1 [B 2 O 3 F] À and ad eep-ultraviolet cutoff edge below 180 nm. The effect of the introduction of Fatoms on the structure ando ptical property of the borateg roup has been investigated;t his sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…The IR spectra of α-Pb 4 B 2 O 7 and β-Pb 4 B 6 O 13 are shown in Fig. S4 ) were both observed [60,61]. This result also matches pretty well with the crystal structure analysis.…”
Section: Resultssupporting
confidence: 84%
“…The IR spectra of α-Pb 4 B 2 O 7 and β-Pb 4 B 6 O 13 are shown in Fig. S4 ) were both observed [60,61]. This result also matches pretty well with the crystal structure analysis.…”
Section: Resultssupporting
confidence: 84%
“…In recent years, the structural chemistry of inorganic crystals has been significantly extended by the incorporation of more anion units, such as [BO 3 ] 3− , [BO 4 ] 5− , [CO 3 ] 2− , [PO 4 ] 3− , [NO 3 ] − , and [SiO 4 ] 4− , etc., which results in various kinds of mixed multiple‐anions compounds, like borate carbonate, borate phosphate, phosphate nitrate, and phosphate silicate, etc. In addition, chemists and material scientists found that the introduction of F atoms with large electronegativity into the crystals can harmonize the ratio of anions and cations to make the crystal structures more flexible and variable [23–25] . Up to now, a series of unique structures of F‐containing borates or carbonate have been reported, some of which have been reported exhibiting novel structure frameworks and excellent functional performances.…”
Section: Figurementioning
confidence: 99%
“…[41] All of the predicted new structures possess very wide band gaps (8. One of the structures with the P2 1 space group (BaB 2 O 3 F 2 -I) has been experimentally synthesized very recently.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…One of the structures with the P2 1 space group (BaB 2 O 3 F 2 -I) has been experimentally synthesized very recently. [41] All of the predicted new structures possess very wide band gaps 3 Fgroup and have colossal SHG coefficients (ca. 4 KDP) that give the direct evidence that the BO 3 F group could generate large SHG effect.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation